Psycho-Physiological Effects of Television Viewing During Exercise. - Rider, Brian C.; Bassett, David R.; Strohacker, Kelley; Overstreet, Brittany S.; Fitzhugh, Eugene C.; Raynor, Hollie A. (Journal of Sports Science & Medicine, 2016)
We propose that enjoyment is an important factor in the adoption and long-term maintenance of exercise. Television (TV) viewing is believed to be a highly enjoyed leisure-time activity, combining it with exercise may make for a more enjoyable exercise experience. The objective of this study was to examine the effects of television (TV) viewing on psychological and physiological variables during a moderate-intensity exercise bout. Twenty-eight insufficiently active (<150 minutes per week of moderate intensity PA and/or 75 minutes of vigorous PA) adults (Age: M = 47.4 ± 7.6 years) participated in this study. Each participant performed three separate 30-minute walking bouts on a motorized treadmill. During each bout, participants watched a program they selected (30-minute scripted show) (self-selected TV condition), a British Broadcasting Corporation (BBC) nature program (standardized TV condition), or no TV program (no TV condition). Participants were unable to select the nature program as their self-selected program, as it was not a 30-minute scripted program. A Polar Heart Rate (HR) monitor and validated surveys on affect and enjoyment were used. Participants reported greater enjoyment of exercise for both self-selected and standardized TV conditions (97.1 ±15.2 and 92.7 ± 15.2), compared to the No TV condition (77.5 ± 13.4, p < 0.001). The two TV conditions resulted in similar levels of focus on TV viewing (self-selected TV: 81.2 ± 19.7; standardized TV: 79.1 ± 14.2, p > 0.05) and dissociation from walking (self-selected TV: 38.1 ± 6.7 and standardized TV: 33.2 ± 3.9); they also resulted in more dissociation than the no TV condition (TV: 72.6 ± 5.6, p = 0.002). The findings indicate that TV viewing, regardless of whether the programming is self-selected or standardized, associates with greater enjoyment of exercise.